Pattern dynamics of a vegetation-water model with saturated effect and diffusion feedback - Bai, Huimin; Fan, Yu-Xuan; Li, Li (Physica A, 2025)
Desertification represents one of the most pressing ecological challenges globally, where vegetation patterns serve as critical indicators of ecosystem resilience and early-warning signatures of ecological degradation. Soil water diffusive feedbacks and saturation water uptake by vegetation are important mechanisms for vegetation-water interactions in arid and semi-arid environments. In this paper, a Klausmeier-type vegetation-water model is investigated to study the mechanism of vegetation pattern formation by incorporating a saturated water absorption term and soil water diffusion feedback. We derive amplitude equations near the Turing bifurcation point, revealing selection criteria and stability conditions for vegetation patterns. Our findings reveal that the saturated water absorption effect induces pattern phase transitions, the feedback mechanism of soil water diffusion accelerates desertification, and precipitation gradients induce the emergence of a bistable coexistence phenomenon. These results provide theoretical insights into the dynamics of vegetation patterns and offer guidance for ecosystem management and desertification control.